1992
DOI: 10.2307/2937092
|View full text |Cite
|
Sign up to set email alerts
|

Competition and the Structure of a Benthic Stream Community

Abstract: The mechanisms structuring benthic stream communities composed largely of highly mobile taxa are poorly known. I studied the role of competition in structuring the benthic community of hard substrates in a coldwater stream dominated by mobile insects that grazed upon periphyton and by relatively sessile filter-feeding insects. I expected competitive interactions among periphyton grazers to be significant and chronic because the community was not subject to frequent flow-related disturbances and grazer densitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(154 citation statements)
references
References 72 publications
4
147
3
Order By: Relevance
“…Many studies have shown that stream invertebrates, including mayflies and stoneflies, reduce algal standing crop and compete for these resources in small streams (e.g. Kohler, 1992;Ledger & Hildrew, 2000b), but we found no evidence for resource depression by either species in this experiment. Weak grazing pressure can be explained by low numerical abundance of consumers, poor match between consumer mouthparts and resource structure, and rates of algal primary production that counteract consumptive losses (e.g.…”
Section: Leuctra Inermiscontrasting
confidence: 53%
See 1 more Smart Citation
“…Many studies have shown that stream invertebrates, including mayflies and stoneflies, reduce algal standing crop and compete for these resources in small streams (e.g. Kohler, 1992;Ledger & Hildrew, 2000b), but we found no evidence for resource depression by either species in this experiment. Weak grazing pressure can be explained by low numerical abundance of consumers, poor match between consumer mouthparts and resource structure, and rates of algal primary production that counteract consumptive losses (e.g.…”
Section: Leuctra Inermiscontrasting
confidence: 53%
“…Ledger & Hildrew, 2000a, b) and mayflies (e.g. Kohler, 1992) characteristic of upland streams, but the extent to which competition occurs between these groups has not been tested within the context of acidification. Specifically, we assessed the degree of resource overlap between Leuctra inermis and Baetis rhodani and, using a field experiment, tested the hypothesis that the growth rate of a recolonist, Baetis, could be affected by Leuctra, its putative competitor.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of variance in chironomids assemblages explained only by hydromorphological variables in our study was considerable (30.8%) and similar to the percentage of variation explained by physicochemical variables (27.7%). The relatively high percentage of unexplained variation (41.5%) in our study is typical of noisy data sets with many 0 values (Borcard et al, 1992), and could be result of abiotic and biotic factors not considered in this study, such as species' interactions (Kohler, 1992), food availability (Peeters et al, 2004), reproduction, competition and predation (MacNeil et al, 1999).…”
Section: Spatial Variability: Hydromorphological and Physicochemical mentioning
confidence: 99%
“…Several factors have been considered as decisive in structuring macroinvertebrate assemblages in streams: substrate (Reice, 1980;Rae, 1985), allochthonous matter (Cummins & Klug, 1979), temperature (Vannote & Sweeney, 1980;Ward & Stanford, 1982), flow (Rabeni & Minshall, 1977;Dudgeon, 1993a), disturbance (Siegfried & Knight, 1977;Death & Winterbourn, 1995), and biotic interactions (Kohler, 1992).…”
Section: Introductionmentioning
confidence: 99%